2003
DOI: 10.14358/pers.69.9.973
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of Lidar and Color Aerial Photography for Mapping Urban Parcel Imperviousness

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 16 publications
0
77
0
3
Order By: Relevance
“…Additionally, LiDAR benefits from a low processing requirement and high spatial resolution [6,7]. LiDAR data has proven competent in improving up to 25% accuracy in differentiating surfaces by means of height [4]. This study area contains asphalt roads and asphalt roofs which possess similar spectral reflectance; therefore, it is necessary to make a distinction between roof and ground surfaces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LiDAR benefits from a low processing requirement and high spatial resolution [6,7]. LiDAR data has proven competent in improving up to 25% accuracy in differentiating surfaces by means of height [4]. This study area contains asphalt roads and asphalt roofs which possess similar spectral reflectance; therefore, it is necessary to make a distinction between roof and ground surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of varied urban surface materials has an impact on the surrounding environment [4,5]. This has requested the detailed accounting of surface materials and its properties, such as magnitude, abundance, location, geometry, and spatial pattern [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus easy to adapt for new datasets, and the classification process is highly automated. In the context of ALS and aerial image data analysis, classification trees have been used, for example, by Hodgson et al [65] for mapping of urban parcel imperviousness, Ducic et al [66] to classify full-waveform laser data, and Jung [13], Matikainen [67], Zingaretti et al [68], Holland et al [8] and Im et al [69] to classify buildings and other classes. The classification tree tools available in the Statistics Toolbox of Matlab were used to implement the classification.…”
Section: Building Detection Methodsmentioning
confidence: 99%
“…For an object in the M1, 1) if it is totally in the interior of the changed areas, its class can only be determined according to the independent classification result from the high resolution image; 2) if this object is intersected with the changed areas, it means that the class type of this object should be consistent with the class type of the intersection areas between this object and unchanged areas. Pervious research show that joint classification with stacked LiDAR data and high resolution image generally has a better performance than the independent classification result yielded by sole sensor data [37]. Thus, the class type of this object is determined by the class extracted from joint classification result located in the intersection between unchanged areas and this object.…”
Section: Object-based Post-classification Fusionmentioning
confidence: 99%
“…Generally, LiDAR data is firstly transformed into a multi-band raster image, and then used as integrated features with high resolution multispectral image for landscape classification [34][35][36]. Previous studies indicated that the combination of LiDAR data and high resolution remote sensing image outperformed that using only high resolution image [24,37,38].…”
Section: Introductionmentioning
confidence: 99%